Fine tuning of nanopipettes using atomic layer deposition for single molecule sensing. Issue 14 (11th June 2015) - Sze, Jasmine Y. Y.; Kumar, Shailabh; Ivanov, Aleksandar P.; Oh, Sang-Hyun; Edel, Joshua B.
Abstract : ALD modified pipettes provides a quick and efficient method for fine-tuning the nanopore diameter which can be used for a broad range of applications including the detection of small biomolecules at the single molecule level. Abstract : Nanopipettes are an attractive single-molecule tool for identification and characterisation of nucleic acids and proteins in solutions. They enable label-free analysis and reveal individual molecular properties, which are generally masked by ensemble averaging. Having control over the pore dimensions is vital to ensure that the dimensions of the molecules being probed match those of the pore for optimization of the signal to noise. Although nanopipettes are simple and easy to fabricate, challenges exist, especially when compared to more conventional solid-state analogues. For example, a sub-20 nm pore diameter can be difficult to fabricate and the batch-to-batch reproducibility is often poor. To improve on this limitation, atomic layer deposition (ALD) is used to deposit ultrathin layers of alumina (Al2 O3 ) on the surface of the quartz nanopipettes enabling sub-nm tuning of the pore dimensions. Here, Al2 O3 with a thickness of 8, 14 and 17 nm was deposited onto pipettes with a starting pore diameter of 75 ± 5 nm whilst a second batch had 5 and 8 nm Al2 O3 deposited with a starting pore diameter of 25 ± 3 nm respectively. This highly conformal process coats both the inner and outer surfaces of pipettes and resulted in the fabrication of pore diameters as low as 7.5 nm. We show that Al2 O3 modified pores do not interfere with the sensing ability of the nanopipettes and can be used for high signal-to-noise DNA detection. ALD provides a quick and efficient (batch processing) for fine-tuning nanopipettes for a broad range of applications including the detection of small biomolecules like RNA, aptamers and DNA–protein interactions at the single molecule level.